Teori Konseling Psikoanalisis: Studi Literatur - Habsy, Bakhrudin All; Nabila Nafis, Bunga Ragil; Emiliasari, Cahya; Ningtyas, Niken Mahara (Lembaga Yasin AlSys, 2024)
Psychoanalytic Counseling is one of the counseling methods that uses psychiatric concepts to help individuals overcome psychiatric/mental/personality problems. The writing of this article discusses the theory of psychoanalytic counseling as a counseling method in solving problems faced by each individual. The method used in writing this article is a qualitative method using literature studies. Data collection by tracing, collecting, analyzing, and understanding data related to academic sources and related research. The final results of writing this article are (1) Historical Perspectives of Psychoanalytic Counseling, (2) Basic Concepts of Psychoanalytic Counseling, (3) Personality Development in Psychoanalytic Counseling, (4) Objectives of Psychoanalytic Counseling, (5) Processes of Psychoanalytic Counseling, (6) Relationship Situations of Psychoanalytic Counseling, and (7) Changing Mechanisms of Psychoanalytic.